A Note on Physical and Mechanical Properties of Mesua assamica (Syn. Kayea assamica) from Darrang Division, Tezpur, Assam - Sekhar, A. C.; Gaharwar, K. S. (Indian Forester, 1977)
Physical and mechaoical tests were done in green and kiln dry conditions on small clear specimens obatained from 7 logs of Mesua assumica received from Darrang Division, Assam. The results obtained have been compareded with Teak.Estimated values based on strength specific gravity formulae have also been compared with observed values in green condition. Safe working stresses and tentative suitability Indices have also been reported and compared with the corresponding values of Teak.